A pH‐Neutral Polyelectrolyte Hole Transport Layer for Improved Energy Band Structure at the Anode/PTB7 Junction and Improved Solar Cell Performance. Issue 11 (23rd September 2021) - Kang, Ju Hwan; Harit, Amit Kumar; Jeong, Ji-Eun; Woo, Han Young; Seo, Jung Hwa; Walker, Bright
Abstract : In organic solar cells (OSCs), interfacial properties between the donor phase and hole transport layers (HTLs) are critical factors which govern charge extraction efficiency. Many ionic and polar materials are known to function as effective interfacial layers; however, an understanding of how ionic moieties affect the electronic band structure and characteristics of OSCs is lacking. Herein, a new, pH‐neutral polyelectrolyte is introduced that resolves several problems which are encountered with the commonly used HTL, poly(3, 4‐ethylenedioxythiopene):polystyrenesulfonate (PEDOT:PSS). An effective p‐type polyelectrolyte dopant is designed, comprising an anionically charged PSS backbone with easily reduced Cu 2+ counterions (Cu:PSS), and interfacial properties for HTL/donor interfaces by photoelectron spectroscopy are analyzed. The effects of the polyelectrolyte on interfacial energy levels and charge extraction efficiency between the active layer and HTL are quantified. Using optimized processing conditions, the efficiency can be improved from 8.31% to 9.28% in conventional OSCs compared with a standard PEDOT:PSS HTL. The energy‐level alignment at the HTLs/donor interface determined by UV photoelectron spectroscopy measurements reveals the origin of distinct differences in device performances. The reduced ionization potential (IP) and hole injections barrier (Φh ) at the HTL/donor interface play a crucial role in efficient charge extraction in conventional OSCs. Abstract : The effects of Cu (II) poly(styrene sulfonate) (Cu:PSS) on the electronic band structure and characteristics of organic solar cells are investigated. Easily reduced Cu 2+ ions balance the negative charges on the PSS backbone, supporting p‐doping at the interface with PTB7. Photoelectron spectroscopy confirms a band‐bending effect, consistent with the observed hole extracting effects of Cu:PSS in solar cells.